(untitled) (LEARNing Landscapes, 2023)
While the terms “schooling” and “education” are often used as if they are synonymous, they name different, yet complementary, aspects of a child’s learning experience. Education is a birth–to-forever process that is undertaken by parents and family members. Schooling is just one part of that education process. To reach desired educational outcomes for students, it is imperative that we step away from “schoolcentric” practices and instead “walk alongside” parents and families as they work to realize their hopes and dreams for their children.